MODEL OF LEGAL DISPUTE RESOLUTION FOR BUSINESS CONTRACT DEFAULT: A STUDY OF VARIOUS CASES LAW - Fahmi, Chairul; Audia Humairah; Ayrin Sazwa (JURISTA: Jurnal Hukum dan Keadilan, 2023)
Business contracts are an essential element underlying every commercial relationship. The contract serves as a legal tool that regulates the rights and obligations of the parties involved in a business transaction. However, in practice, business contract disputes often occur, either due to a mismatch in understanding of the contents of the contract, violation of the contract provisions, or changes in conditions that affect the implementation of the contract. This research is a qualitative research with a normative juridical approach, where the main data is obtained from primary data sources in the form of laws, and legal doctrines. The results of this study indicate that default occurs when the debtor does not fulfil obligations according to the agreement, which has an impact on business relations. In addition, ethics in civil law enforcement, particularly in business contracts, are important to maintain the integrity of the legal system. Ethics, which include the principles of justice, truth, and integrity, serve as the foundation for law enforcement.